A Note on Essential Components and Essential Weakly Efficient Solutions for Multiobjective Optimization Problems. (30th December 2009) - Luo, Qun
Abstract : The concept of essential component of weakly efficient solution set is introduced first. Then we obtain some sufficient conditions for the existence of an essential component or an essential weakly efficient solution in the weakly efficient solution sets for multiobjective optimization problems.